2009
DOI: 10.1186/1758-2652-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Network for HIV Drug Resistance Surveillance: a survey of individuals recently diagnosed with HIV

Abstract: Use of antiretrovirals is widespread in Brazil, where more than 200,000 individuals are under treatment. Although general prevalence of primary antiretroviral resistance in Brazil is low, systematic sampling in large metropolitan areas has not being performed.The HIV Threshold Survey methodology (HIV-THS, WHO) was utilized, targeting Brazil's four major regions and selecting the six most populated state capitals: Sao Paulo, Rio de Janeiro, Salvador, Porto Alegre, Brasilia and Belem. We were able to sequence sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
65
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 30 publications
14
65
2
2
Order By: Relevance
“…We hypothesized that HIV-1 subtype C was in some way more fit for the HLA/KIR genetic background of the local population than HIV-1 subtype B. However, although the subtype frequency distribution in our study (C = 63%; B = 31%; F = 4%; and CRF02 = 3%) was consistent with previous data [41,42], we did not find viral load or T-CD4 decay differences between subtype B and C in relation to KIR genotype or HLA-B alleles. It is still possible that differences in the incidence rate of the two subtypes in southern Brazil are due to some as yet unrecognized epidemiological nuance, a multifactorial process of the dissemination including human mobility, accessibility, and local founder events [43]or perhaps an intrinsic biological characteristic of subtype C viruses, similar to that found in a study that suggested a greater mucosal transmission [44] of subtype C as well as faster accumulation of drug resistance mutations in subtype C isolates [45].…”
Section: Discussionsupporting
confidence: 67%
“…We hypothesized that HIV-1 subtype C was in some way more fit for the HLA/KIR genetic background of the local population than HIV-1 subtype B. However, although the subtype frequency distribution in our study (C = 63%; B = 31%; F = 4%; and CRF02 = 3%) was consistent with previous data [41,42], we did not find viral load or T-CD4 decay differences between subtype B and C in relation to KIR genotype or HLA-B alleles. It is still possible that differences in the incidence rate of the two subtypes in southern Brazil are due to some as yet unrecognized epidemiological nuance, a multifactorial process of the dissemination including human mobility, accessibility, and local founder events [43]or perhaps an intrinsic biological characteristic of subtype C viruses, similar to that found in a study that suggested a greater mucosal transmission [44] of subtype C as well as faster accumulation of drug resistance mutations in subtype C isolates [45].…”
Section: Discussionsupporting
confidence: 67%
“…1). [2][3][4][5] However in the Southern region, a distinct profile is observed. Currently, depending on the state, 27-79% of HIV infections are caused by HIV-1C, 23-45% by HIV-1B, 3-29% by CRF31 BC and other BC recombinants, and HIV-1F and its recombinants account for up to 10% of infections.…”
Section: Introductionmentioning
confidence: 88%
“…Individuals infected with viruses carrying multiple drug resistance mutations may have reduced survival prospects, and for this reason, estimates of the rate at which drug resistance mutations are transmitted are a key target metric of the World Health Organization (WHO) HIVDR threshold survey . This survey has revealed that fewer than 5% of HIV transmissions in lowerincome countries such as Malawi (Kamoto et al 2008), Tanzania, Ethiopia, Swaziland, South Africa, Thailand, and Vietnam involve the transmission of viruses carrying known drug resistance mutations, whereas specific areas of Brazil and China have transmitted drug resistance mutation rates between 5% and 15% (Booth et al 2007;Inocencio et al 2009;Liao et al 2010). The prevalence of transmitted HIV drug resistance (TDR) in developing countries is lower than that in developed countries, where in some countries, such as the United States, rates of transmitted drug resistance within newly diagnosed antiretroviral naïve HIV-1-infected individuals are in the range of 15% (Wheeler et al 2010).…”
Section: Hiv Genetic Diversity and Drug Resistancementioning
confidence: 99%